The Urban Warming Causes and Adaptation in Tropical Cities - M. Kali Hamzah Siregar; Muhammad Sani Roychansyah (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH))
Urban warming indicate that urban would be hotter than rural areas because of the urban heat island. Unfortunately, Tropical urban people are considered to be used to hot temperature. In addition, various research indicate that this condition may affect to thermal discomfort and other problems for human life. Therefore, this research will describe and explain the causes of urban warming in tropical cities and the adaptation mechanism conducted by citizen so that city government can find better solution to adapt with urban warming. To get better overview, Kuala Lumpur, Malaysia and Medan City, Indonesia become the comparison sample. The data derived from previous research result and observation using google earth satellite imagery which are analyzed descriptively and spatially. The result shows that both cities experience urban warming because of the land use and urban morphology. but, regarding with adaptation, Medan City still adapt traditionally like watering the road but in Kuala Lumpur, City government prioritize the negotiation and technological approach.